Archeological Survey of the Sulphur Spring Valley, Southeast Arizona - Woosley, Anne I.; Price, Tim; D. Carol Kriebel (The Amerind Foundation, Inc., 1987)
The Willcox Playa Study grew from the realization that though surveys had been initiated in the Sulphur Spring Valley during the early days of Southwestern archeology, scarcely any subsequent work was undertaken, with the result that southeastern Arizona remains one of the least known regions of the prehistoric Southwest. We felt that a project would fill a gap in our knowledge of the area and would also contribute generally to Southwest archeology. The fact that the playa area is in the backyard, so to speak, of the Amerind Foundation made it doubly desirable since its proximity enables us to sustain a long range study much more easily than if we were faced with the logistics of a distant project area. The greater playa region is ideal for archeological investigation because it contains the remains of a Pleistocene lake and known artifacts of Paleo-lndian origin plus materials belonging to all later prehistoric stages. This ensures that the long prehistoric sequence is, indeed, represented by archeological remains. The recoverable data base provides excellent opportunities to document the earliest occupations of the Southwest, to reconstruct a prehistoric framework of many thousands of years, and to understand cultural changes over the long term. There exist few localized areas that potentially encompass such chronological depth, a situation which makes for exciting research prospects. These were some of our thoughts when we embarked on the 1984 reconnaissance survey. Our preliminary five-week effort established in our minds the need for much more intensive survey. Hence, application for a grant-in-aid from the State Historic Preservation Office to support a more extensive survey in 1985. A report incorporating results from both 1984 and 1985 was presented to the State Historic Preservation Office (Woosley and Kriebel, 1985). Though these two season produced a wealth of information, it was apparent that further work was required if the entire temporal range of prehistoric site remains was to be documented. As physical conditions deteriorated and the land became increasingly more arid, settlements shifted from one locality to another across the northern Sulphur Spring Valley. This displacement of prehistoric populations within the valley meant that a great deal of ground, much more than was first anticipated, had to be surveyed in order to record sites representing the whole of the prehistoric chronological sequence. Consequently, another proposal was submitted to the State Historic Preservation Officer in 1985 for an additional phase of archeological survey. This funding supported the 1986 field work which is summarized in the following chapters. The immediate objective of the 1986 season was to continue our inventory of prehistoric and historic archeological resources in the Sulphur Spring Valley. We added to the previously initiated site inventory (1984 and 1985) by extending the study area to include additional significant environmental/topographic zones, including the Pat Hills, the foothills of the Dragoon Mountains, and the Turkey Creek drainage, thereby providing a more complete picture of the general prehistoric settlement pattern. Such survey will assist us in ultimately estimating site density and site locational selection processes in broad chronological terms of Archaic peoples, early ceramics communities, and later farm villages.